A systematic review and meta‐analysis of interventions to increase physical activity in children and adolescents with intellectual disabilities. Issue 4 (26th December 2017) - McGarty, A. M.; Downs, S. J.; Melville, C. A.; Harris, L.
Abstract: Background: Increasing physical activity (PA) through intervention can promote physical and mental health benefits in children and adolescents. However, children and adolescents with intellectual disabilities (ID) have consistently been shown to engage in low levels of PA, which are insufficient for long‐term health. Despite this, little is known about the effectiveness of interventions to increase PA in children and adolescents with ID. The aims of this study were therefore to systematically review how effective interventions are at increasing PA levels in children and adolescents with ID and to further examine what components have been used in these interventions. Method: A systematic search of MEDLINE, EMBASE, Education Resources Information Center, Cumulative Index to Nursing and Allied Health Literature, PsychINFO, Cochrane Central Register for Controlled Trials and International Standard Randomised Controlled Trial Number trials registry was conducted (up to July 2016). Articles were included if they met the following eligibility criteria: children and adolescents (<18 years) with ID, measurement of PA at baseline and post‐intervention and intervention studies. Effect sizes were calculated as standardised mean difference ( d ) and meta‐analysis calculated between intervention and no treatment control intervention. Results: Five studies met the eligibility criteria and were included in the review. Study design, methodological quality and intervention components were varied. Interventions did not support sufficient changes in PA to improve health. The meta‐analysis demonstrated that intervention groups were not more effective at increasing PA levels post‐intervention ( d : 2.20; 95% CI −0.57 to 0.97) compared with control. However, due to a decrease in PA in the control intervention, a moderate significant effect was demonstrated at follow‐up ( d : 0.49; 95% CI 0.14 to 0.84). Conclusions: There is a lack of studies which aim to increase PA levels in children and adolescents with ID, with current interventions ineffective. Future studies are required before accurate recommendations for appropriate intervention design and components can be made.